Avaliação da auto-associação molecular de complexos metálicos com ligantes triazenidos derivados do 1,3-bis(fenil)triazeno - Villis, Paulo Cesar Mendes (2007)
This work presents the synthesis and the investigation of the crystalline and molecular structure of 1,3-bis(2-methoxy-4-nitrophenyl)triazene ethanol and seventeen new mononuclear or binuclear complexes of Cu(I), Cu(II), Tl(I), Hg(II), Ag(I), Ni(II), Zn (II) with monocatenated triazenide ligands derived from the 1,3-bis(phenyl)triazene. The coordination of metallic ions by triazenido compounds had been studied in the solid state. We studied the relations that make possible the formation of intramoleculares and intermoleculares interactions, that could show supramolecular arrangements unidimensionais, bidimensional and until three-dimensional. Other eight ligands had been synthesized and we investigated its physical and molecular properties: 1,3-bis (3-nitrophenyl)triazene, 1,3-bis(4-methoxycarbonylphenyl)triazene, 1,3-bis(4-ethoxycarbonylphenyl)triazene, 1,3-bis(4-chlorophenyl)-triazene, 1-(phenyl)-3-(4-nitrophenyl)triazene, 1-(4-chlorophenyl)-3-(4-nitrophenyl)triazene, 1-(2-methoxy-4-nitrophenyl)-3-(2,4-dibromophenyl)triazene and 1-(4-nitrophenyl)-3-(2-pyrimidinyl) triazene. We used techniques of Infrared Absorption Spectroscopy, Spectrometry of Nuclear Magnetic Resonance, Melting Point and Elementary Analysis CHN in this study. The variety in the geometry of coordination of the 1,3-bis(2-methoxy-4-nitrophenyl)triazene can be used to depicted its versatility to form complexes with many metallic ions, beyond presenting a variety of chemical and spectroscopic properties. The complexes {Cu[CH3O(NO2)C6H3NNNC6H3(NO2)OCH3]}4(CH3CN)4 (1), {Cu[CH3O(NO2)C6H3NNNC6H3(NO2)OCH3(C5H5N)2(N3)]}(3) and {Cu[CH3O(O2N)C6H3NNNC6H3(NO2)OCH3-(C5H5N)2(CH3COO)]} (4), using the copper ion (I and II) had been characterized by Spectroscopy of Electronic Paramagnetic Resonance, Electronic and Electrochemical Spectroscopy. All these complexes of Cu (II) had presented interesting magnetic and electrochemical properties.